Replicability of the Silicon Valley in the North Shore City : a thesis presented in fulfilment of the requirements for the degree of Master of Management at Massey University - Simicic, Zlatko (Massey University, 2003)
Over the past decade the theory of Industrial Cluster (Porter, 1990; 1998a) has received a significant attention because of its seeming promise to change the regional economies into thriving centers of wealth and innovative excellence comparable in success to celebrated places such as Silicon Valley in San Francisco Bay area. Porter (1990; 1998a) argues that such places derive their strength from geographic concentrations of highly specialized companies that are both competing and collaborating. In his view those concentrations also lead to increased interdependencies of firms through value chain relationship and expert knowledge spillover which are further factors that also attract new companies to locate in vicinity and thus in process enhance synergetic effects of the region. This thesis provides an alternative view which, being based on local conditions, argues that concentration of specialized firms does not necessarily, implies dynamics that lead toward kind of industrial cluster described by Porter. Specifically, this thesis argues that cultural foundation play a key role in determining the degree of interfirm connectedness and whether the business collaborative dynamics and interconnectedness seen in Silicon Valley will take place. Similarly, this thesis argues that concentration of specialized companies does not have to be driven by business enhancing factors of Porter's diamond model and that may be merely driven by lifestyle concerns and needs of entrepreneurs themselves.
Keywords: North Shore City (N.Z.); High technology industries; Space economics; Industrial location; United States; Cluster analysis